The effect of electron bite-outs on artificial electron heating and the PMSE overshoot. - Belova, E.; Kassa, M.; Havnes, O. (European Geosciences Union, 2005)
We have considered the effect that a local reduction in the electron density (an electron bite-out), caused by electron absorption on to dust particles, can have on the artificial electron heating in the height region between 80 to 90 km, where noctilucent clouds (NLC) and the radar phenomenon PMSE (Polar Mesospheric Summer Echoes) are observed. With an electron density profile without biteouts, the heated electron temperature Te,hot will generally decrease smoothly with height in the PMSE region or there may be no significant heating effect present. Within a biteout Te,hot will decrease less rapidly and can even increase slightly with height if the bite-out is strong. We have looked at recent observations of PMSE which are affected by artificial electron heating, with a heater cycling producing the new overshoot effect. According to the theory for the PMSE overshoot the fractional increase in electron temperature Te,hot/Ti , where Ti is the unaffected ion temperature = neutral temperature, can be found from the reduction in PMSE intensity as the heater is switched on. We have looked at results from four days of observations with the EISCAT VHF radar (224MHz), together with the EISCAT heating facility. We find support for the PMSE overshoot and heating model from a sequence of observations during one of the days where the heater transmitter power is varied from cycle to cycle and where the calculated Te,hot/Ti is found to vary in proportion to the transmitter power. We also looked for signatures of electron bite-outs by examining the variation of Te,hot/Ti with height for the three other days. We find that the height variation of Te,hot/Ti is very different on the three days. On one of the days we see typically that this ratio can increase with height, showing the presence of a bite-out, while on the next day the heating factor mainly decreases with height, indicating that the fractional amount of dust is low, so that the electron density is hardly affected by it. On the third day there is little heating effect ...